Notification of crop varieties and registration of germplasm - Agrawal, P. K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Vivek Dhan 157 (VL 8302) is a June sown rainfed upland rice (Oryza sativa L.) variety developed by the Vivekananda Parvatiya Krishi Anusandhan Sansthan, Almora. It is derived from the cross VR 9588/A-57. It was recommended for release by the ‘Variety Identification Committee’ held on April 6th, 2014 at the Directorate of Rice Research, Hyderabad during the 49th Annual Rice Research Group Meeting for the low elevated hills of Meghalaya and mid-hills of Uttarakhand. It was released and notified by the Central Sub-committee on Crop Standards vide notification number SO 1543 dated 31th July 2014 for cultivation in the low elevated hills of Meghalaya and mid-hills of Uttarakhand. Farmers from different hill states would certainly prefer this variety because of high grain yield, resistance against blast, high HRR and grain quality. The specific area of its adaptation of this variety is the rainfed kharif, both under high and low fertility in the Northern hills of Uttarakhand and Meghalaya.